2010
DOI: 10.1007/s00018-009-0256-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity of autoantibodies from patients with epidermolysis bullosa acquisita with murine collagen VII

Abstract: The pathomechanism of antibody-mediated tissue damage in autoimmune diseases can be best studied in experimental models by passively transferring specific autoantibodies into animals. The reproduction of the disease in animals depends on several factors, including the cross-reactivity of patient autoantibodies with the animal tissue. Here, we show that autoantibodies from patients with epidermolysis bullosa acquisita (EBA), a subepidermal autoimmune blistering disease, recognize multiple epitopes on murine col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…We further showed that all antibodies generated here, which were directed to different epitopes of human COL7 NC1, led to dermal-epidermal separation ex vivo, as reported previously using other fragments of COL7 (Csorba et al, 2010). Split formation was dependent on the presence of neutrophils, whereas incubation of human skin with antibodies alone did not cause pathology.…”
Section: Discussionsupporting
confidence: 83%
“…We further showed that all antibodies generated here, which were directed to different epitopes of human COL7 NC1, led to dermal-epidermal separation ex vivo, as reported previously using other fragments of COL7 (Csorba et al, 2010). Split formation was dependent on the presence of neutrophils, whereas incubation of human skin with antibodies alone did not cause pathology.…”
Section: Discussionsupporting
confidence: 83%
“…The recombinant fragments designated GST-mCXVII-EC1, GST-mCXVII-EC3, GST-mCXVII-EC7 and GST-mCXVII-IC2 contain murine collagen XVII sequences stretching from amino acid positions 498–580, 856–901, 1030–1134, and 186–475, respectively [31]. These GST-fusion proteins containing sequences of murine BP180/CXVII were cloned and purified as previously described [31], [41]. Briefly, recombinant GST fusion and His-tagged proteins were expressed in E. coli TOP10 and XL1-Blue and purified by gluthatione agarose and metallochelate affinity chromatography, respectively as described [16], [42].…”
Section: Methodsmentioning
confidence: 99%
“…Six-micrometer cryosections of murine or human skin were washed in PBS to remove embedding medium and incubated with 100 µl of diluted antibody preparations for 2–3 h at 37°C. Sections were washed twice with PBS and chambers were prepared as previously described [41]. Human leukocytes were isolated from the peripheral blood of healthy donors.…”
Section: Methodsmentioning
confidence: 99%
“…Rabbit immune complexes were formed using a recombinant form of mouse collagen VIIC (GST-mCVIICr) and sera from a rabbit immunized against this protein [21]. Briefly, 96-well microtiter plates were coated with 5 g of GST-hCXVII-NC16A or 5 g of GST-mCVIICr in 0.1 M bicarbonate buffer (pH 9.6).…”
Section: Ros Measurement By Luminol Chemiluminescencementioning
confidence: 99%
“…The ability of BP patients' autoantibodies to activate human and murine leukocytes was assessed using an ex vivo assay of antibodyinduced granulocyte-dependent dermal-epidermal separation in cryosections of normal human skin, as described previously [21,22].…”
Section: Ex Vivo Cryosection Assaymentioning
confidence: 99%